CONSTRUÇÕES DO IMAGINÁRIO RELIGIOSO NO CULTO A INANNA NA ANTIGA MESOPOTÂMIA: SÍMBOLOS E METÁFORAS DE UMA DEUSA MULTIFACETADA (3200-1600 a.C) - Dupla, Simone Aparecida (2016)
Inanna, the multifaceted goddess of Mesopotamian culture, was worshiped throughout the history of this society. Known as the goddess of love and war, their status in the Mesopotamian pantheon and its functionality has been re-reading object by many historians. The purpose of this study was to address the representations present in the worship of Inanna through symbols and attributes to it attributed unveiling its characteristics and relationship with the imagery of that society. To do this, we use as sources, in addition to recorded images for artifacts, myths and hymns dedicated to this deity. We realize that the ways of holiness expressed in the worship of Inanna allowed the articulation of this in many social segments and ensured their maintenance and survival. Thus, images and symbols that made up the religious universe of divinity were assignments and constructions that are perpetuated over time related to the reality of his first devotees and those who captivated over the millenniums.